Interaction of Paddy Varieties and Compost with Flux of Methane in Tidal Swampland - Abduh, Andin Muhammad; Annisa, Wahida (JOURNAL OF TROPICAL SOILS, 2016)
Varieties and organic materials have a very important role to the flux of methane (CH4) on paddy cultivation, especially on wetlands. Purpose of this research to determine the amount of methane emissions that released from paddy cultivation in acid sulphate soils with the use of different varieties and paddy straw composting. Acid sulfate soil samples taken Experimental Farm Swampland Agricultural Research Center (BALITTRA), Tanjung Harapan, District Alalak, Barito Kuala, South Kalimantan. This research uses Randomized Complete Design of two factors. The first factor is the use of paddy varieties and the second factor is the use of paddy straw compost. Research shows that there is a very real interaction between the two factors. Treatment varieties Inpara 3 + without paddy straw compost releases CH4 flux most low at 0,030 mg.m-2.day-1, while treatment Inpari 30 + paddy straw compost 5 Mg. ha-1 release most CH4 flux is 0.571 mg. m-2.day-1.